2018
DOI: 10.1037/sgd0000279
|View full text |Cite
|
Sign up to set email alerts
|

Parent responses to childhood gender nonconformity: Effects of parent and child characteristics.

Abstract: Many children display traits, interests, or behaviors not stereotypically associated with their sex. Little is known about the factors influencing how parents respond to their children engaging in gender-nonconforming behaviors, yet the way parents respond to such behaviors may be critical to supporting children's development-particularly among children who frequently display gender-nonconforming traits and behaviors. This study examined parent and child characteristics that relate to how parents respond, or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 31 publications
1
17
1
2
Order By: Relevance
“…Fathers of children AFAB were less likely to feel ambiguous loss (Coolhart et al, 2017). These findings are consistent with evidence that parents have more discomfort with gender diverse behaviors in AMAB children compared with AFAB children (Spivey et al, 2018). Men are also known to react less positively to TGD youth when samples are controlled for religious affiliation, conservative political views, and traditional views of gender (Elischberger et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Fathers of children AFAB were less likely to feel ambiguous loss (Coolhart et al, 2017). These findings are consistent with evidence that parents have more discomfort with gender diverse behaviors in AMAB children compared with AFAB children (Spivey et al, 2018). Men are also known to react less positively to TGD youth when samples are controlled for religious affiliation, conservative political views, and traditional views of gender (Elischberger et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown how parents who were uncomfortable with their child’s gender non-conforming behaviours, and intervened to change their gender back to their birth-assigned sex, did so in order to force their child to meet their societal gender expectations [ 45 ]. Previous research also showed that in gender-atypical youth, half of their parents tried to change their behaviours [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents should accept, respect, and appreciate youth from a diverse set of gender expressions [ 25 ]. Research suggests that providing interventions to increase parental support for gender non-conforming youth could have a positive effect on well-being [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the association between gender-nonconforming behavior and more emotional problems for boys only is that the strength and nature of gendered expectations may differ for the sexes, for example, gender nonconformity may be less accepted in boys than girls, both by other children (e.g. Conry-Murray, Kim, & Turiel, 2015) and by parents (Spivey, Huebner, & Diamond, 2018). Stigma processes may then contribute to poorer mental health.…”
Section: Childhood Gender Nonconformity and Emotional Problemsmentioning
confidence: 99%